Assessment framework for pavement material and technology elements in green highway index - Bujang, Mastura; Hainin, Mohd Rosli; Abd Majid, Muhd Zaimi; Mohd Satar, Mohd Khairul Idham; Wan Azahar, Wan Nur Aifa (Elsevier, 2018)
Sustainability concept in highway development needs to be addressed critically in order to alleviate the effect of global warming and depletion of natural resources issues. In Malaysia, there are a lot of alternative pavement materials and technology that have been introduced to the industry so that green highway can be achieved. However, Malaysia does not have any tools to assess the level of greenness for any highway projects and still lacks of awareness in sustainable highway. Thus, the main objective of this study is to develop an assessment framework for pavement material and technology elements in Malaysia green highway index. An extensive literature were reviewed and expert discussion was conducted to identify the 13 vital elements of pavement material and technology which include regional materials; reuse of top soil; reused and/or recycled of non-hazardous materials; earthwork balance; usage of industrial by-products; subgrade improvement/soil stabilization, permeable pavement, pavement design life, quiet pavement, recycled pavement or new sustainable techniques; cool pavement; soil biotechnical engineering treatment; and green techniques. Questionnaires were distributed among the 109 highway practitioners to obtain their agreement level on these elements. Then, all the data were analyzed by using factor analysis approach which generated from Statistical Package for Social Science (SPSS) software. The assessment score of each element was calculated from the findings and assessment framework for pavement material and technology elements was established. Results show that all the elements were grouped into four main factor namely environmental control, economical resources, innovation technology and erosion control with four point was considered as a maximum point score to be achieved in green highway assessment framework. Hence, the research clearly indicates that these elements are essential to be implemented in Malaysia's highway development indirectly as an encouragement to improve the performance of transportation sector.